Catalyst-controlled regioselectivity in phosphine catalysis: the synthesis of spirocyclic benzofuranones via regiodivergent [3 + 2] annulations of aurones and an allenoate. Issue 8 (21st June 2017) - Ni, Huanzhen; Yu, Zhaoyuan; Yao, Weijun; Lan, Yu; Ullah, Nisar; Lu, Yixin
Abstract : Catalyst-controlled regiodivergent [3 + 2] annulations of aurones and allenoates have been developed. Abstract : Catalyst-controlled regiodivergent [3 + 2] annulations of aurones and allenoates have been developed. When a dipeptide phosphine catalyst with anl-d - configuration was employed, α-selective [3 + 2] annulation products could be obtained with good regioselectivities and enantioselectivities. With the employment ofl-l - dipeptide phosphines, γ-selective annulation products could be selectively obtained with excellent enantioselectivities. By simply tuning the catalyst configurations, a wide range of α-selective or γ-selective spirocyclic benzofuranones with either aryl or alkyl substitutions could be readily prepared. DFT calculations suggest that the conformation of the dipeptide phosphines influences the hydrogen bonding interactions or the distortion energy, resulting in delicate energy differentiation in the transition states, and accounting for the observed regioselectivity.